Short-term outcomes of surgical resection and radiofrequency in treatment of hepatocellular carcinoma - Alshimaa M.M Eid; Hoda A.A Youssef (Wolters Kluwer Medknow Publications, 2020)
Backgroundand aim To evaluate surgical liver resection in comparison with radiofrequency in the treatment of early hepatocellular carcinoma (HCC) regarding intraoperative blood loss and transfusion, time of respectability, time of operation, ICU stay, hospital stay, postoperative morbidity, mortality, and overall survival. Introduction Surgical resection and radiofrequency ablation (RFA) in the treatment of HCC are different modalities for the treatment of HCC. Patients and methods This is a prospective study that included 60 patients with HCC randomized into hepatic resection and RFA groups at Al-Zahraa University Hospital from 2016 to 2019. Demographic and biochemical characteristics, intraoperative data, postsurgical complications, and overall survival rate were compared between groups. Results Surgical resection group had longer operative time, resection time, blood loss and blood transfusion, hospital stay, and ICU stay than RFA group. Postoperative hemorrhage, bile leak, and chest infection were markedly decreased in RFA group than surgical resection group. Wound infection and ascites are similar in the two patient groups. Regarding the median follow-up during the 3 years, there were no significant differences between the treatment groups in 1- and 3-year overall survival. Conclusion Surgical resection is considered the primary solution if the patient's liver function and general conditions are good enough to undergo surgical intervention. RFA is considered superior to hepatic resection in the treatment of HCC in terms of operation duration and other complications like hemorrhage and bile leak. RFA revealed similar overall survival to surgical resection. RFA is accessible and a promising liver resection method with very good results.